Pemahaman Hadis Toleransi Beragama - Yanto, Sukono Andri; Muhajirin, Muhajirin; Nur, Sulaiman Muhammad (Hikmah, 2024)
Indonesia as a country with diverse cultures, ethnicities and religions is expected to uphold the values of religious tolerance. However, reality shows that the understanding of tolerance often experiences an imbalance between the Radicalism group that is fanatical about differences in religious teachings and the liberalism group that is too excessive so that it exceeds the limits. This phenomenon is interesting to study, especially through the lens of hadith as one of the important sources of Islamic law in understanding religious tolerance. By using the hadith analysis method and referring to various related references, the author tries to explore and understand the meaning of religious tolerance through the perspective of hadith. This research aims to provide a new view in balancing the understanding of tolerance in the midst of existing diversity, with the hope of realising better religious tolerance in Indonesia. The results explain that an understanding of hadith based on its historical context can be a solid foundation in finding solutions and resolving religious conflicts that exist in Muslim societies, as well as making an important contribution to social harmony in Indonesia. This research has implications for the construction of the concept of religious tolerance from the hadith perspective, which is relevant to be applied as a material for community development in modern times.